The Internationalization Agenda of African Universities in the Next Decade - Andoh, Harris; Salmi, Jamil (International Higher Education, 2019)
Since the late 2000s, a growing number of African universities have put the international dimension at the heart of their strategic agenda. Flagship and national universities have created offices for deputy vice chancellors or directors, directorates, and centres for internationalization and strategic partnerships, and moved from a narrow focus on student mobility programs to research partnerships with universities in industrial countries as a way of building their capacity and improving their position on the global stage.